The Utilization of Picture Booklets to Cultivate The Young – Indonesian Slow Learners’ English Speaking Ability - Mas Muhammad Idris; Dyah Setyowati Ciptaningrum (Department of Early childhood Education, 2018)
In post-modernity era, the English communication skill must be highlighted as a vital item to attain one’s own target of language learning process gained not only from formal education but also non-formal one. Hence, it may lead all of the educators around the world to strengthen the English speaking proficiency which can be employed through many activities in their language regular classrooms and Indonesian educators are no exception as well to do so. Consequently, the roles of educators become very important due to their challenges to find out a means of teaching approaches that enable stimulating the slow and normal learners to comprehend the materials given by their educators. However, this paper solely focuses on the Young-Indonesian slow learners who need special treatments in their language learning process to at least catch up the average point of their study by using the picture booklets (PBs) to develop their English speaking competence. And therefore, the five core characteristics of slow learners have also been discussing in it in order to facilitate the educators easy to indicate and educate them properly. In addition, the two teaching strategies namely the compensatory teaching (CT) and remedial teaching (RT) are indeed as fundamental approaches too to cultivate the Young-Indonesian slow learners’ English speaking ability.